2016
DOI: 10.1007/s12593-012-0074-y
|View full text |Cite
|
Sign up to set email alerts
|

The Biomechanical and Histological Effects of Diabetes on Tendon Healing: Experimental Study in Rats

Abstract: The aim of this study was to investigate the biomechanical and histological perspectives of healing of Achilles tendon in diabetic rats and compare the results with non-diabetic subjects. Fifty four adult Wistar Albino rats weighing 300-350 g were used throughout the study. Six animals were excluded from the study and replaced. Rats were randomly assigned to either the experimental or the control group comprised of 24 rats in each. Diabetes was induced in experimental group with streptozotocin. 3 days after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The number of inflammatory cells, blood vessels, and proliferating cells were lower; the deposition and structural organization of collagen fibers and proteoglycans were impaired and the expression of MMPs was dysregulated in diabetic animals compared with the nondiabetic animals after tendon injury (Appendix S3). Osteochondroid metaplasia was noticed in the diabetic group but not in the nondiabetic group as early as day 15 57 and week 6 58 after Achilles tendon transection and repair in rat models. The delayed healing responses have implications on the early and more frequent development of tendinopathy after microtrauma and the poor prognosis of tendinopathy in diabetic patients.…”
Section: Pathological Changes In Tendon In Diabetic Patientsmentioning
confidence: 87%
“…The number of inflammatory cells, blood vessels, and proliferating cells were lower; the deposition and structural organization of collagen fibers and proteoglycans were impaired and the expression of MMPs was dysregulated in diabetic animals compared with the nondiabetic animals after tendon injury (Appendix S3). Osteochondroid metaplasia was noticed in the diabetic group but not in the nondiabetic group as early as day 15 57 and week 6 58 after Achilles tendon transection and repair in rat models. The delayed healing responses have implications on the early and more frequent development of tendinopathy after microtrauma and the poor prognosis of tendinopathy in diabetic patients.…”
Section: Pathological Changes In Tendon In Diabetic Patientsmentioning
confidence: 87%
“… 1 Previous studies have shown the regenerative capability of tendons to be compromised in patients with diabetes because of less fibroblast proliferation and lymphocyte infiltration in healing tendons associated with tendon weakness. 1 , 3 , 6 An animal study indicated that DM impairs tendon-bone healing after rotator cuff repair. 2 Several clinical studies have further investigated the relationship between DM and retearing of the rotator cuff tendon.…”
mentioning
confidence: 99%
“…Disorders of healing are observed at the structural, biochemical and molecular level. Healing tendons in diabetic individuals exhibit worse biomechanical properties: reduced stiffness, reduced tensile stress, reduced maximum load, decreased Young's modulus . Young's modulus is also known as the elastic modulus and is defined as the quotient of stress (MPa) and strain (proportional deformation) in a material.…”
Section: Ligament and Tendon Injuries In Patients With Dmmentioning
confidence: 99%
“…In the inflammatory phase of healing, significant reduction of neutrophil and macrophage infiltration at the lesion site was observed . In turn, the proliferative phase is characterized by decreased amounts of fibroblast and lymphocyte infiltration, therefore, cell proliferation is limited. There is also a decrease in vascularization in the early proliferative phase (evaluated on the 7th day after injury, unchanged on the 28th day) .…”
Section: Ligament and Tendon Injuries In Patients With Dmmentioning
confidence: 99%
See 1 more Smart Citation